Normal and slow learners: a new discriminative method based on the speed of spatial learning in aged mice - Duffau, Céline; Hadzibegovic, Senka; Andelkovic, Vojislav; Bontempi, Bruno; Nicole, Olivier (Frontiers in Aging Neuroscience, 2025)
Aging is accompanied by a decline in cognitive functions, including spatial memory, yet significant variability exists in the learning abilities of older individuals. Using a large cohort of aged and young male mice, we employed spatial discrimination testing in an 8-arm radial maze to investigate age-related differences in performance in spatial learning and to categorize individual memory phenotypes within the aged population. Despite a general learning ability across groups, aged mice showed slower acquisition rates compared to young counterparts, highlighting age-related cognitive difficulties in establishing or discriminating spatial representations. By modeling individual learning curves, we classified aged mice into two subgroups—normal learners (NL) and slow learners (SL)—based on learning speed. SL mice demonstrated significantly delayed spatial memory acquisition compared to NL and young mice, suggesting pronounced heterogeneity in cognitive aging. This method provides a robust framework to explore the neurobiological underpinnings of learning deficits and may inform the development of targeted interventions to mitigate age-related memory decline.